(untitled) (Research, Society and Development, 2020)
Although orchids are of great environmental and economic importance, there are few scientific studies on alternative disease control, which represent a major problem for producers and growers. An alternative sustainable control strategy is the use of extracts from plants. The objective of this work was to evaluate an antifungal activity of plant extracts without control of Rhizoctonia sp. isolated orchid. From orchids with symptoms of Rhizoctonia sp., Or the adjustment was isolated and repeated, with subsequent verification of the gender level, based on macro and microscopic changes. Then, the antifungal potential of aqueous extracts of mastic (Schinus terebenthifolius Raddi), gaucho (Mikania glomerata Spreng), tuia (Thuja occidentalis Lineu) and sesame (Sesamum indicum Lineu) were evaluated. The bioassay was conducted in a randomized experimental design in a 4 x 3 factorial scheme (four plant extracts and three doses each). As tested tests were 0, 10 and 20%, with 15 repetitions each. There was greater mycelial inhibition of Rhizoctonia sp. by the aqueous extracts of tuia and guaco with a concentration of 20%, showing antifungal activity of 19.84 and 14.74%, respectively.